Patrimoine, généalogie et identité : la valorisation de la mémoire familiale au Québec et en Acadie au XXe siècle - Caroline-Isabelle Caron (Enfances, Familles, Générations, 2007)
In this article we discuss the contribution of XIX-XX century genealogy in Quebec and Acadia to the creation of a symbolic patrimony. The knowledge of their genealogical background is a precious asset for those members of the family who identify with their past ; and its value is great enough to require that they preserve and transmit it to future generations. Genealogy nourishes a process of “distinction” (in the sense given to it by Bourdieu) in both the genealogist and his or her family. Those who recognize themselves in their family history differentiate and distinguish themselves from others whose family history differs from theirs.